Effect of Noni Fruit (citrifolia L.) on Blood Glucose Levels of Male Diabetic Rattus Norvegicus Rats - Wijaya, Caroline Shereen Aurelia; Andisari , Hendrata Erry; Risma, Risma (Journal La Medihealtico, 2023)
Diabetes is a persistent metabolic disorder characterized by disruptions in both insulin secretion and action, leading to heightened blood glucose levels (hyperglycemia). Noni fruit, rich in antioxidant compounds like flavonoids and alkaloids, is thought to possess anti-diabetic properties. This study aimed to assess the influence of administering 500 mg/kgBW of noni fruit on the glucose levels of Wistar rats induced with diabetes using 150 mg/kgBW of alloxan. Blood sampling followed a post-test only group method conducted before terminating the mice. The study involved 33 mice divided into three groups: a negative control group, a positive control group induced with diabetes for 3 days, and a treatment group induced with diabetes followed by a 14-day administration of noni fruit extract. The normality test revealed a non-normal distribution with a p value <0.05. Additionally, the Kruskal-Wallis test resulted in a p value <0.05, signifying the impact of noni fruit administration on the blood glucose levels of rats. The Mann-Whitney U test indicated a p value > 0.05 between the positive control group and the treatment group. Despite the absence of a significant difference in glucose levels between the two groups, the study concluded that administering noni fruit at a dose of 500 mg/kgBW could influence the blood glucose levels of mice.